Behavioural and physiological responses to predators of captive-bred Arctic charr : significance of genetics, learning and ontogeny - Laakkonen, Mika (Helsingin yliopisto, 2010)
Predation forms one of the main selective forces in nature and in a vast number of prey species the behavioural responses form the main way to avoid predation. World wide numerous captive breeding programs are used to produce fish and other animal species for conservational reintroductions. However, rearing animals in the absence of predators in captivity has been shown to weaken their predator avoidance skills and lead to behavioural divergence between wild and captive-bred populations. In my thesis I studied the effects of predator odour exposures on antipredator behavioural and physiological responses of captive reared Saimaa Arctic charr. This charr population is the most endangered fish population in Finland and a sample of the remaining population has been taken to captive breeding and used for an extensive reintroduction program. Lowered responsiveness to predators is probably one of the major reasons for the poor survival probability of the charr after release into the wild. The main aims of my thesis were to explore the reasons for behavioural phenotypic variation in this charr population and whether naïve charr young could be trained to recognise their natural predators. The predator species in my thesis were burbot (Lota lota) and pikeperch (Sander lucioperca). In my thesis I showed that the captive-bred charr responded to chemical cues from burbot and pikeperch, but the magnitude of responses was linked to the predator species. The burbot odour increased the spatial odour avoidance of the charr young. On the other hand, in the pikeperch treatment charr reduced their relative swimming activity and tended to show more freezing behaviour relative to the burbot treatment. It seems evident that these different responses are related to the different hunting tactics of predator species. Furthermore, I detected wide between-family differences in antipredator responsiveness (i.e. inherited variation in antipredator behaviours) in this captive stock. Detected differences were greater in the response towards ...